Perlindungan dan Eksistensi Sistem Gelar Adat Masyarakat Palembang di Era Milenial - Tohir, Muhammad (Universitas Sriwijaya, 2022)
In the chapter 18 b, article 2 UUD 1945 that State admitted and respected to Adat Community United and Principle of Indonesian Republic United. Adat title is symbol given by someone or group that existension is admitted in Adat law community. In other area, adat title is given to make and keep on connecting between lineal group. And then Adat title given influence to rights and obligation is especially at territorial right and living to providing physical and spiritual sustanance. Problem solving that is How does mechanism in protecting of adat title at the law Adat Palembang community system at the milinial era. This research metode use normatif and empris catagories. This research matrials are interview and library system and Those are as sources of research data. The Analysis are combining between interview and library research data so that to be formulated as The written. The Conclution, the protection of adat law title system on the Palembang law community united of the milimial era has been done by parties, the First party is Culture departement as apart of region goverment of Palembang that supervised right and the second party is Dewan Pembina Adat ( Traditional council), is function in building of adat law title system. The Palembang traditional council is led by Sultan Mahmud Badaruddin, and the last is lead by Pemangku adat as village and sub-district council. The risistance of protecting in law adat title Palembang system are looked by Juridice, sociologyst and philosophist views. Because of dualism rule system and there is not special law in regulating law title given system yet, is not funtion, benificial and behavior of adat title used.